Psychological Well-Being and Care Giver Burden of Parents Having Child with Leukemia : Psychological Well-Being & Care Giver Burden of Parents - Ghaffar, Robina; Ali, Afsar; Sarwar, Hajra (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2023)
Leukemia is one of most prevalent type of cancer among the children with age less than 15 years. Worldwide, Leukemia represents 32.5% of all types of cancer among the children. In Pakistan, 46.5% child with cancer diagnosed with leukemia. Both the mother and father are involved in the direct and indirect care of their child with leukemia Direct care is the tasks with the care of the child with leukemia and indirect care is the financial support and the facilities provided to the patients. Objective: To determine the psychological wellbeing and Care burden among parents having Children with Leukemia. Methods: A cross-sectional study designed was used. A sample of n=81 participants was recruited from Sadiq Abbasi Hospital Bahawalpur, through convenient sampling. The psychological wellbeing and care burden questionnaires were used to measure care burden and psychological wellbeing among parents having children with leukemia. Filled questionnaires were entered and analyzed through SPSS version-21. Results: Findings revealed that 71.60% participants had poor psychological wellbeing, 18.51% had fair and only 38.27% had good wellbeing during their children leukemia care. Similarly, 12.34% had low care burden, 38.27% had moderate and majority 49.38% were having high care burden. Conclusions: Majority of the parents of children with leukemia in this study were having high care burden and poor psychological wellbeing while taking care of their children